Gastric cancer and Helicobacter pylori infection. - Clarkson, K S (1993)
AIMS--To identify differences in the prevalence of Helicobacter pylori infection in different groups of patients with gastric cancer. METHODS--In total 224 cases of gastric cancer were studied: 120 (53.6%) intestinal; 69 (30.8%) diffuse; and 35 (15.6%) unclassified. Site of tumour, presence and severity of gastritis, presence and extent of intestinal metaplasia, and age and sex were also recorded. Infection by H pylori was assessed using modified Giemsa staining. RESULTS--H pylori infection was found in 96 (43%) cases. There was no significant association between infection and histological type of tumour, nor was there any significant association between infection and site of tumour, the presence of intestinal metaplasia, age, or sex. The only significant association identified was between infection and gastritis. CONCLUSIONS--These results are in broad agreement with those of other similar studies, although the overall prevalence of infection, at 43%, was lower than has been reported in some series. The findings do not support a role for H pylori in any particular subgroup of patients with gastric cancer but do not exclude a role for the organism in the pathogenesis of gastric cancer as a whole.